Piceatannol mediated regulation of deregulated signaling pathways in different cancers: Tumbling of the ninepins of molecular oncology - Nayyab, Sawera; Naureen, Humaira; Maryam, Areesha; Attar, Rukset; Sabitaliyevich, Uteuliyev Yerzhan; Konysbayevna, Konysbayeva Kenzhekul; Farooqi, Ammad Ahmad (Cellular and Molecular Biology, 2020)
With the recent technological advancements, a new golden era of natural products drug discovery has dawned. Increasingly it is being realized that structural modularity of many pharmacologically active products derived natural sources allows a building-block approach which can be exploited for analysis of regulation of deregulated oncogenic protein networks in different cancers. Piceatannol has been shown to effectively modulate JAK/STAT, Wnt/Î²-catenin, mTOR pathway in different cancers. In addition, certain hints have emerged which shed light on the regulation of microRNAs by piceatannol in some cancers. Regulation of deregulated oncogenic pathways by Piceatannol is gradually capturing attention and might be helpful in the multi-targeting of deregulated oncogenic networks in cancers.